A Scoping Review of Ethical Considerations in Spiritual/Religious Counseling and Psychotherapy. (June 2019) - Maximo, Sally I.
Four overarching themes from this scoping review were identified, namely: (a) clients' right for autonomy and self-determination; (b) cultural sensitivity; (c) practitioner competency issues; and (d) recommended guidelines for ethical practice. These themes were aligned with the moral principles that guide professional ethical practice. A competency-based model was designed based on findings to enhance counselor/clinician competencies by enhancing sensitivity to spiritual and religious sentiments, which allows greater responsiveness to the clients' needs, values and preferences.